Phase II study of pembrolizumab and capecitabine for triple negative and hormone receptor-positive, HER2−negative endocrine-refractory metastatic breast cancer - Ami N Shah; Lisa Flaum; Irene Helenowski; Cesar A Santa-Maria; Sarika Jain; Alfred Rademaker; Valerie Nelson; Dean Tsarwhas; Massimo Cristofanilli; William Gradishar (Journal for ImmunoTherapy of Cancer)
Background Response rates to single agent immune checkpoint blockade in unselected pretreated HER2−negative metastatic breast cancer (MBC) are low. However, they may be augmented when combined with chemotherapy.Methods We conducted a single-arm, phase II study of patients with triple negative (TN) or hormone receptor-positive endocrine-refractory (HR+) MBC who were candidates for capecitabine. Patients were treated with pembrolizumab 200 mg intravenously day 1 and capecitabine 1000 mg/m2 by mouth twice daily on days 1–14 of a 21-day cycle. The primary end point was median progression-free survival (mPFS) compared with historic controls and secondary end points were overall response rate (ORR), safety and tolerability. The study had 80% power to detect a 2-month improvement in mPFS with the addition of pembrolizumab over historic controls treated with capecitabine alone.Results Thirty patients, 16 TN and 14 HR+ MBC, were enrolled from 2017 to 2018. Patients had a median age of 51 years and received a median of 1 (range 0–6) prior lines of therapy for MBC. Of 29 evaluable patients, the mPFS was 4.0 (95% CI 2.0 to 6.4) months and was not significantly longer than historic controls of 3 months. The median overall survival was 15.4 (95% CI 8.2 to 20.3) months. The ORR was 14% (n=4), stable disease (SD) was 41% (n=12) and clinical benefit rate (CBR=partial response+SD>6 months) was 28% (n=8). The ORR and CBR were not significantly different between disease subtypes (ORR 13% and 14%, CBR 25% and 29% for TN and HR+, respectively). The 1-year PFS rate was 20.7% and three patients have ongoing responses. The most common adverse events were low grade and consistent with those seen in MBC patients receiving capecitabine, including hand-foot syndrome, gastrointestinal symptoms, fatigue and cytopenias. Toxicities at least possibly from pembrolizumab included grade 3 or 4 liver test abnormalities (7%), rash (7%) and diarrhea (3%), as well as grade 5 hepatic failure in a patient with liver metastases.Conclusions Compared with historical controls, pembrolizumab with capecitabine did not improve PFS in this biomarker unselected, pretreated cohort. However, some patients had prolonged disease control.Trial registration number NCT03044730.